Analisis Tantangan dan Strategi Guru dalam Pembelajaran Diferensiasi Kurikulum Merdeka di SDN 106811 Bandar Setia - Nur Aulia Heriani; Tessa Lonika Simanullang; Ekaristi Br Sembiring; Elsani Hutabarat; Joshua Manurung; Dwi Anisa Saraan; Lala Jelita Ananda; Asiah Ramadhani (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This research aims to analyze the challenges faced by teachers in implementing the Merdeka Curriculum at SDN 106811 Bandar Setia, particularly in differentiated learning, and to identify strategies that can be applied to overcome these challenges. The research method used is a qualitative approach with the research subject being a sixth-grade teacher. Data was collected through observation and semi-structured interviews, then analyzed using thematic analysis techniques. The research results indicate that the main challenges include the lack of teacher understanding in preparing Merdeka learning lesson plans, the lack of understanding of learning models that are based on Merdeka learning, and the lack of teacher innovation in the learning process. Strategies that can be applied to overcome these challenges include increasing teacher competence, developing flexible materials, and using diagnostic assessments.